Pengaruh Kualitas Pelayanan, Kepercayaan, Dan Harga Terhadap Kepuasan Pelanggan Pengguna Jasa Ekspedisi J&T Express (Studi Pada Mahasiswa FEB UNISMA Angkatan 2018) - Imamiatur Rofiqoh; Siti Asiyah; Alfian Budi Primanto (UNIVERSITAS ISLAM MALANG, 2022)
AbstractThis study aims to examine and explain the effect of service quality, trustworthiness, and price on customer satisfaction using J&T Express expedition services to study FEB Unisma students. This research is an explanatory research type with a quantitative approach. The method used is multiple linear regression. The sampling technique used the formula from Malhotra with the calculation results of 75 samples. To solve the problem in this study using SPSS assistance with validity test, reliability test, normality test, multiple linear regression analysis, multicollinearity test, heteroscedasticity test, F test, and t test. The results showed that simultaneously the variables of service quality, trust, and price had an effect on customer satisfaction. And there is a partial influence between the variables of service quality, trust, and price on customer satisfaction. Keywords: service quality, trust, price, customer satisfaction